Potential Neuroimmune Interaction in Chronic Pain: A Review on Immune Cells in Peripheral and Central Sensitization - Yang, Jia-Xuan; Wang, Hong-Fei; Chen, Ji-Zhun; Li, Han-Yu; Hu, Ji-Chen; Yu, An-An; Wen, Jun-Jun; Chen, Si-Jia; Lai, Wei-Dong; Wang, Song; Jin, Yan; Yu, Jie (Frontiers in Pain Research, 2022)
Chronic pain is a long-standing unpleasant sensory and emotional feeling that has a tremendous impact on the physiological functions of the body, manifesting itself as a dysfunction of the nervous system, which can occur with peripheral and central sensitization. Many recent studies have shown that a variety of common immune cells in the immune system are involved in chronic pain by acting on the peripheral or central nervous system, especially in the autoimmune diseases. This article reviews the mechanisms of regulation of the sensory nervous system by neutrophils, macrophages, mast cells, B cells, T cells, and central glial cells. In addition, we discuss in more detail the influence of each immune cell on the initiation, maintenance, and resolution of chronic pain. Neutrophils, macrophages, and mast cells as intrinsic immune cells can induce the transition from acute to chronic pain and its maintenance; B cells and T cells as adaptive immune cells are mainly involved in the initiation of chronic pain, and T cells also contribute to the resolution of it; the role of glial cells in the nervous system can be extended to the beginning and end of chronic pain. This article aims to promote the understanding of the neuroimmune mechanisms of chronic pain, and to provide new therapeutic ideas and strategies for the control of chronic pain at the immune cellular level.